2014
DOI: 10.1002/2014gl061668
|View full text |Cite
|
Sign up to set email alerts
|

Climate controls how ecosystems size the root zone storage capacity at catchment scale

Abstract: The root zone moisture storage capacity (S R ) of terrestrial ecosystems is a buffer providing vegetation continuous access to water and a critical factor controlling land-atmospheric moisture exchange, hydrological response, and biogeochemical processes. However, it is impossible to observe directly at catchment scale. Here, using data from 300 diverse catchments, it was tested that, treating the root zone as a reservoir, the mass curve technique (MCT), an engineering method for reservoir design, can be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
245
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(250 citation statements)
references
References 61 publications
4
245
0
1
Order By: Relevance
“…Major regulators of forest evapotranspiration include forest biomass (Feng et al, 2016), leaf stomatal conductance (Lin et al, 2015), canopy leaf area index (LAI) (Mu et al, 2013), tree hydraulic traits (Gao et al, 2014) and stand surface roughness (Donohue et al, 2007). In the context of temperate and boreal Sweden, changes in forest attributes are likely to play an important role because of the higher proportion of available energy partitioned into latent heat than in other ecosystems in these regions, such as grassland, wetlands and tundra (Baldocchi et al, 2000;Kasurinen et al, 2014;van der Velde et al, 2013).…”
Section: F Jaramillo Et Al: Dominant Effect Of Increasing Forest Bimentioning
confidence: 99%
“…Major regulators of forest evapotranspiration include forest biomass (Feng et al, 2016), leaf stomatal conductance (Lin et al, 2015), canopy leaf area index (LAI) (Mu et al, 2013), tree hydraulic traits (Gao et al, 2014) and stand surface roughness (Donohue et al, 2007). In the context of temperate and boreal Sweden, changes in forest attributes are likely to play an important role because of the higher proportion of available energy partitioned into latent heat than in other ecosystems in these regions, such as grassland, wetlands and tundra (Baldocchi et al, 2000;Kasurinen et al, 2014;van der Velde et al, 2013).…”
Section: F Jaramillo Et Al: Dominant Effect Of Increasing Forest Bimentioning
confidence: 99%
“…Recently, the BH has been widely used to investigate the interannual variability of precipitation partitioning (Gerrits et al, 2009), separation of runoff trends (H.-Y. Xiong et al, 2015), evapotranspiration change (Savenije, 1997) and water storage change (Istanbulluoglu et al, 2012;Gao et al, 2014). These studies show that hydrological processes have been greatly affected by the climate change and intensive change of land cover owing to human activities.…”
Section: Du Et Al: Role Of Water Balance In An Extended Budyko Hymentioning
confidence: 99%
“…A potentially effective starting point for the latter is to use observations at the modelling scale to infer information about the functional shapes and to quantify the actual parameters of individual processes at that scale. Examples include the concept of master recession curves (Lamb and Beven, 1997) or the water holding capacity in the unsaturated root zone (S U,max ), which is the core of many hydrological systems as it controls the partitioning of drainage and evaporative fluxes (Gao et al, 2014b;de Boer-Euser et al, 2016;Nijzink et al, 2016b). These system components integrate heterogeneities and quantify actual physical properties present and physical processes active at the observation and modelling scale.…”
Section: Modelling Myths -Or Not?mentioning
confidence: 99%
“…A recent example includes , who identified dominant process controls underlying regional differences in regime and flow duration curves. Similarly, Gao et al (2014b) demonstrated how the model parameter representing the water storage capacity in the unsaturated root zone at the macroscale can be considerably constrained exclusively based on water balance data.…”
Section: Organized Complexity and Catchment Similaritymentioning
confidence: 99%